Chloroplast genomes of key species shed light on the evolution of the ancient genus Isoetes. Issue 3 (29th December 2020) - Pereira, Jovani B. S.; Giulietti, Ana Maria; Pires, Eder S.; Laux, Marcele; Watanabe, Maurício T. C.; Oliveira, Renato R. M.; Vasconcelos, Santelmo; Oliveira, Guilherme
Abstract: Although phylogenetic studies have revealed major clades, the deepest relationships in Isoetes remain unresolved. The use of next‐generation sequencing provides enormous amounts of gene sequences, which allows not only clarification of the basal relationships but also rapid radiations. Plastomes of six key Isoetes species were annotated, revealing a total of 129 or 130 genes, depending on the species. Our phylogenomic analyses comprising representatives of all major clades yielded well‐supported nodes and identical topologies using maximum likelihood and Bayesian inference. The phylogenetic reconstructions detangled the deep relationships in Isoetes and illuminated the more recent radiations in the genus. A basal dichotomy was found that grouped Isoetes spp . from Brazil and South Africa into a clade sister to the remaining Isoetes groups. Interestingly, I. andicola was found to be sister to the North American species complex. Genomic trait mapping analysis showed that the missing introns in the atpF and clpP genes were well conserved in two major clades. The absence of trnK‐UUU was observed in the Brazilian tropical species and in I. velata . Among lycophytes, the gene trnR‐CCG was missing only in I. eludens . In general, genomic traits such as the presence or absence of internal stop codons, a tRNA, and an intron were revealed to be conserved within groups, suggesting that these genomic traits might reveal vital information about the evolution of the genus. This study will contribute to understanding the diversification of Isoetes and the establishment of a better framework to address the evolutionary history of the genus. Abstract : Although phylogenies have revealed major groups, deep relationships in the genus Isoetes and the overall chloroplast genome architecture of its groups remain unclear. This study assembled chloroplast genomes for six species from distinct phylogenetic and taxonomic groups in Isoetes . Our study showed an overwhelming evolutionary stasis in the chloroplast genome of Isoetes . However, despite its conservative nature, the chloroplast genome provided enough DNA data to establish deep relationships in the genus. Furthermore, minor plastomic traits revealed to be conserved within groups, suggesting that they might reveal vital information about the evolution of the genus. Our study provides the most robust framework to understand the evolution of the chloroplast genome in Isotes .